Truck Fleet Evaluation for Mechanistic – Empirical Pavement Design Method - Buhari, Rosnawati (International Journal of Integrated Engineering, 2019)
The Mechanistic-Empirical (M-E) pavement design and maintenance method requires a prediction of actual distribution of dynamic load caused by the fleet of trucks that travels on particular section of the road. In this study, the importance of the dynamic nature of the load on the evolution of the real vertical profile was evaluated by performing both static and dynamic calculation using vehicle-truck dynamic-interaction approach. Several truck parameters were considered include type of axle, loading condition, axle configuration, vehicle speed etc. The results indicate that dynamic wheel loads generated by 1/3 loading trucks are the most variable or non-uniformed than others due to uncertainties in body bounce generated by the truck which are strongly influence by surface irregularities. Although the importance of developing truck fleet evaluation approach for (M-E) pavement design are not on the road irregularities individually, besides vehicle speed, loading condition and suspension types should be considered thoroughly.